Income inequality and health: Evidence from developed and developing countries - Dierk Herzer; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2014)
We assess the effect of income inequality on life expectancy by performing separate estimations for developed and developing countries. Our empirical analysis challenges the widely held view that inequality matters more for health in richer countries than for health in poorer countries. Employing panel cointegration and conventional panel regressions, we find that income inequality increases life expectancy in developed countries. By contrast, the effect on life expectancy is significantly negative in developing countries. While the quantitative effects are small, the striking contrast between the two country groups proves to be robust to modifications in measurement, specification and methodological choices.
Keywords: I14; C23; 330; Health; Inequality; Panel cointegration